Adaptive modulation and subcarrier allocation for multiuser OFDM/CDMA systems - Zhang, Hua (2008)
Orthogonal frequency-division multiplexing (OFDM) is a promising technology to resist Intersymbol Interference (ISI) for transmitting data at extremely high rates, splits up the data stream and sends the data symbols simultaneously at a drastically reduced symbol rate over a set of parallel subcarriers. The focus of this thesis is on the adaptive modulation and subcarrier allocation methods for single- and multi-service transmissions with limited transmitted power in the Multi-Carrier DS-CDMA (called OFDM/CDMA in this thesis) system.